A clinical study of keratomycosis to compare the efficacy of topical 10% NaCl with 5% natamycin versus 5% natamycin alone as a treatment strategy - Jitendra Kumar ,; Naveen Sirohi,; Apurva Jain, (Asian Journal of Medical Sciences, 2023)
Background: Corneal blindness is a major public health problem worldwide and preventable cause of blindness in India. Corneal blindness is the second most common cause of blindness, after cataract, in developing countries. Aims and Objectives: A clinical study of keratomycosis to compare the efficacy of topical 10% NaCl with 5% natamycin (Group A) versus topical 5% natamycin (Group B) alone as a treatment strategy. Materials and Methods: This prospective, randomized, interventional, and comparative study with parallel design enrolled 100 cases diagnosed with unilateral keratomycosis and fulfilling the inclusion criteria, who presented to the outpatient department of Ophthalmology, Maharani Laxmi Bai Medical College and Hospital, Jhansi, Uttar Pradesh, between April 2021 and June 2022 (15 months). Results: Maximum patients in both the study groups belonged to the age group of 41–50 years showed male preponderance and belonged to the low socioeconomic status. Maximum patients in both the study groups had shown total regression in 66 cases with 41 cases from Group A and 25 cases from Group B, respectively. Regression was not seen in 34 cases with 9 cases belonging to Group A and 25 cases belonging to Group B. Maximum patients in study Group A had shown ulcer regression in 3.56 average weeks duration, while it was in 4.50 average weeks duration in Group B. Conclusion: This comparative and interventional study demonstrates that the study Group A receiving 10% sodium chloride solution with 5% natamycin helps in faster healing of corneal ulcer, rate of progression of ulcer is slowed down, and complications are less in comparison to Group B receiving 5% Natamycin alone owning to the anti-edema property of hypertonic saline. Hence, topical 10% NaCl solution can be used with 5% natamycin, as a cost-effective adjunct in the management of fungal keratitis.